Continuous Improvement in Nursing Education through Total Quality Management (TQM) - Tang Wai Mun; Muhammad Faizal A. Ghani (Intelektual Pustaka Media Utama, 2013)
Total Quality Management (TQM) has generally been validated as a crucial revolution in the management field. Many academicians believe that the concept of TQM is applicable to academics and provides guiding principles towards improving education. Therefore, an increasing number of educational institutions such as schools, colleges and universities have started to embrace TQM philosophies to their curricula.Within the context of TQM, this paper would explore the concept of continuous improvement by using the Deming philosophy. Subsequently, this paper would elaborate on the application of TQM to bring about continuous improvement in the current education system.